2024
DOI: 10.1038/s41419-024-06759-7
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced energy metabolism in the tumor margin mediated by RRAD promotes the progression of oral squamous cell carcinoma

Aoming Cheng,
Qiaoshi Xu,
Bo Li
et al.

Abstract: The tumor margin as the invasive front has been proven to be closely related to the progression and metastasis of oral squamous cell carcinoma (OSCC). However, how tumor cells in the marginal region obtain the extra energy needed for tumor progression is still unknown. Here, we used spatial metabolomics and the spatial transcriptome to identify enhanced energy metabolism in the tumor margin of OSCC and identified that the downregulation of Ras-related glycolysis inhibitor and calcium channel regulator (RRAD) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Cheng et, al. found that the energy metabolism of the tumor margin in oral squamous cell carcinoma was more active, and the cells in the tumor margin produced more ATP to address the higher metabolic costs for invasion using spatial metabolomics and the spatial transcriptomics [ 83 ].…”
Section: Integration Of Spatial Transcriptomics With Other Omicsmentioning
confidence: 99%
“…Similarly, Cheng et, al. found that the energy metabolism of the tumor margin in oral squamous cell carcinoma was more active, and the cells in the tumor margin produced more ATP to address the higher metabolic costs for invasion using spatial metabolomics and the spatial transcriptomics [ 83 ].…”
Section: Integration Of Spatial Transcriptomics With Other Omicsmentioning
confidence: 99%